Introduction to Artificial Intelligence - Ertel, Wolfgang (Springer, 2017)
After 60 years, Artificial Intelligence (AI) has now reached industry and the consciousness of the population. The impressive successes and new AI methods are now so relevant that they should be taught even in a basic course. In about 30 new pages, I report mainly on deep learning, a consistent further development of neural networks, which finally enables image processing systems to recognize almost any object in pixel images. Among other benefits, this lead to the first computer program that could beat one of the world’s best Go players. In the new section on Deep Learning, we must not leave out a short report about the fascinating new subarea of creativity. For the first time neural networks can creatively generate texts, music pieces, and even paintings in the style of the old masters. These achievements are based on many years of research on neural networks and machine learning. Practical AI has developed into an engineering discipline in which programs are developed in large industrial teams by experts from various specializations. Self-driving cars, service robots, and smart homes—which are all applications of AI—will greatly change our lives. However, in addition to great rays of hope, there will be a dark side. Though we live in a time of rapid technological progress, we have long since exceeded the limits of growth. We must therefore think about sustainability when implementing each new invention. In Chap. 1, I would like to give you some food for thought about this topic. Other new additions to the book include a section on performance evaluation of clustering algorithms and two practical examples explaining Bayes’ theorem and its relevance in everyday life. Finally, in a section on search algorithms, we analyze the cycle check, explain route planning for car navigation systems, and briefly introduce Monte Carlo Tree Search. All known errors have been corrected and updates have been made in many places. I would like to sincerely thank the readers who have given me feedback and all those who contributed to this new edition through proofreading and suggestions.